Facile synthesis of water-stable magnetite nanoparticles for clinical MRI and magnetic hyperthermia applications. (December 2010) - Maity, Dipak; Chandrasekharan, Prashant; Yang, Chang-Tong; Chuang, Kai-Hsiang; Shuter, Borys; Xue, Jun-Min; Ding, Jun; Feng, Si-Shen
Aims: Superparamagnetic magnetite nanoparticles have been under intensive investigation in nanomedicine. However, it is still a challenge to synthesize high-quality water-stable magnetite nanoparticles for better magnetic performance and less side effects in medical MRI and nanothermotherapy.Materials & methods : We successfully synthesized hydrophilic magnetite nanoparticles through thermal decomposition of Fe(acac)3 in triethylene glycol, which were coated with a triethylene glycol layer and thus demonstrated excellent water stability.Results: The optimized deposition temperature has been found to be 250°C (IO-250 NPs). The magnetic and thermal properties as well as the cytotoxicity of IO-250 NPs were investigated. In vitro experiments have demonstrated high cellular uptake and low cytotoxicity. The hyperthermia experiments showed effectiveness in temperature rise and cancer cell death. IO-250 NPs showed promising MRI with relaxivity r2 * as high as 617.5 s -1 mM -1 Fe. In vivo MRI showed excellent tumor imaging.Conclusion: The IO-250 NPs have great potential to be applied for clinical MRI and magnetic thermotherapy.